2014
DOI: 10.1016/j.jjcc.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of eicosapentaenoic acid to arachidonic acid is a critical risk factor for acute coronary syndrome in middle-aged older patients as well as younger adult patients

Abstract: Lower level of EPA/AA is a common critical risk factor for ACS in middle-aged older patients as well as younger adult patients. Some of the risk factors for the onset of ACS in younger patients were different from those in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…A previous report has indicated that AA levels in smokers (mean age, 50 years) are decreased [17], which is inconsistent with the findings of our study; however, another report indicated that AA in smokers are not decreased [18]. Of note, the metabolism of AA is not always parallel to that of EPA [1921], and compared to EPA, smoking has been shown to delay the conversion rate of AA to eicosanoids [22]. These findings may support an impairment of EPA/AA balance, namely, a decrease in the EPA/AA ratio, observed among smokers in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous report has indicated that AA levels in smokers (mean age, 50 years) are decreased [17], which is inconsistent with the findings of our study; however, another report indicated that AA in smokers are not decreased [18]. Of note, the metabolism of AA is not always parallel to that of EPA [1921], and compared to EPA, smoking has been shown to delay the conversion rate of AA to eicosanoids [22]. These findings may support an impairment of EPA/AA balance, namely, a decrease in the EPA/AA ratio, observed among smokers in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In patients with angina pectoris who received statins for 8 months after PCI, the EPA/AA ratio was negatively correlated with the percentage change from baseline in both plaque volume (r ¼ À0.19; P ¼ 0.05) and plaque fibrous component volume (r ¼ À0.21; P ¼ 0.04) [75]. A low EPA/AA ratio was identified as an independent risk factor for ACS in patients !50 years of age as well as in younger adults [76]. In ACS patients assessed by optical coherence tomography, a low EPA/AA ratio was associated with vulnerable coronary plaque morphology, showing a significant correlation with fibrous cap thickness (r ¼ 0.37; P ¼ 0.002) [77].…”
Section: Effects Of Epa On Inflammation and Cytokinesmentioning
confidence: 95%
“…Indeed, the EPA:AA ratio has been shown to be a critical risk factor for ACS. In a study of patients who underwent coronary angiography, a lower EPA:AA ratio was found to be a strong independent risk factor for ACS (odds ratio, 0.37; P = 0.023) [28]. In a second study, a lower EPA:AA ratio correlated with age at the time of ACS onset in patients who were admitted for PCI, suggesting that this ratio is a predictive risk factor for early onset of ACS [61].…”
Section: Acute Coronary Syndromementioning
confidence: 99%